Construction and layout of automobiles and internal-combustion engines : study guide - Klymenko, V. I.; Voronkov, O. I.; Leontiev, D. M.; Mykhalievych, M. H.; Yaryta, O. O.; Ponikarovska, S. V.; Borzenko, O. P.; Fandieieva, A. Ye.; Клименко, В. І.; Воронков, О. І.; Леонтьєв, Д. М.; Михалевич, М. Г.; et al. (ФОП Бровін О. В., 2023)
This publication describes the design and operation of mechanisms, units and systems of cars and internal combustion engines for the purpose of teaching and self-training of university students in the direction of "mechanical engineering" and "transport" in the scope of the curriculum.
Конструкція та будова автомобілів і двигунів внутрішнього згоряння : навчальний посібник
Keywords: automobile; vehicle; internal-combustion engine; ICE; construction of automobiles; construction of vehicles; construction of internal-combustion engines; автомобіль; транспортний засіб; двигун внутрішнього згоряння; ДВЗ; конструкція автомобілів; конструкція транспортних засобів; конструкція двигунів внутрішнього згоряння; 629.022